Factors Associated with Failure of Botulinum Toxin Injection in Adductor Spasmodic Dysphonia. (October 2020) - Zhao, Kevin; Guillaud, Martial; Hu, Amanda
Objective: Electromyography (EMG) Guided botulinum toxin (BTX) injection is considered first-line treatment for adductor spasmodic dysphonia (SD). Failure rate can range between 6% and 29%. Study objective was to determine which factors were associated with failure. Methods: This was a retrospective review conducted at a tertiary, academic center. Adductor SD patients presenting for BTX injections from August 2017 to October 2018 were eligible. Age, gender, Voice Handicap Index (VHI-10), Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V), number of injections, disease duration, unilateral/bilateral injection, right/left injection, dose quantity, body mass index (BMI), professional voice user, employment, psychiatric comorbidity, breathiness, and dysphagia were investigated. Outcomes included failure as defined by the patient and dosage change. Univariate and multivariate statistical analysis was conducted. Results: Sixty seven out of 564 injections (12%) were categorized as failure by 131 patients. In multivariate analysis, dosage change was associated with shorter duration of good effect ( P < .001), BTX dose ( P = .016), breathiness ( P < .001), bilateral injection ( P = .024), dysphagia ( P = .012) and professional voice user ( P = .021). Failure was associated with first injection with a new physician ( P < .001), professional voice user P < .001) and lack of breathiness ( P = .003). Failure rate was not associated with age, gender, VHI-10, CAPE-V, disease duration, left/right injection, dose quantity, BMI, psychiatric comorbidity, and dysphagia. Conclusion: Failure rate was 12% and associated with patients' first injection with a physician, professional voice user, and lack of breathiness. Dosage change occurred in 29% of injections and was associated with injection side effects, bilateral injections, BTX dose, professional voice user, and shorter duration of good effect. Level of evidence: 3